Data Warehouse to Support the Decision Using Vikor Method - Heri Muhrial; Bambang Purnomosidi.D.P; Widyastuti Andriyani; Hamdani Hamdani (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
Data warehouse is a place where data compilations are stored extensively and periodically. The ability of the data warehouse to integrate data lightens CV. Visi Indonesia Mandiri companies in evaluating and making decisions on operational, strategic and tactical processes. The problem is that the company has not provided a data warehouse yet. Moreover, there is no service to give out the needs of easy, consistent, valid and accurate information on operational data, tactical data and strategic data from the decision-making process at the executive level. The data warehouse architecture was established as decision making using the Vikor method analysis.